Efficient and stable perovskite solar cell prepared based on modified lead iodide and preparation method thereof
During the preparation of perovskite solar cells, lead iodide is modified with pentamine acetic acid to form a high crystallinity perovskite film, which solves the film quality problems caused by the instability of the precursor solution and achieves a highly efficient and stable perovskite solar cell.
Patent Information
- Application Number
- CN202411820781.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-11
- Publication Date
- 2025-03-25
AI Technical Summary
During the preparation process, the existing perovskite solar cells have low crystallinity and poor repeatability due to the instability of the precursor solution, which affects the performance and stability of the device.
By adding pentamine acetic acid (PenAAc) to lead iodide as a modification material, a modified lead iodide film was formed, and a spin coating method and thermal annealing technology were combined to prepare a perovskite film with high crystallinity and low defect density.
The high conversion efficiency (24.64%) and good stability of perovskite solar cells are achieved, which reduces non-radiative recombination, accelerates carrier transmission, and improves the overall performance of the device.
Smart Images

Figure CN119698163A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the field of new energy manufacturing technology, and specifically relates to a method for preparing an efficient and stable perovskite solar cell based on modified lead iodide and a method for preparing the same Background Art
[0002] Currently, perovskite films are mainly prepared using solution-based methods, including one-step method, two-step method, thermal evaporation and blade coating technology. Extensive studies have shown that the instability of perovskite precursor solutions is the key factor leading to low reproducibility. The factors that lead to the instability of precursor solutions are mainly related to the state of the precursor solution, such as colloid size, chemical composition and intermediate phase, which affect the crystallinity, grain size, trap density, and ultimately the performance and reproducibility of PSCs. The changes in perovskite precursors are mainly caused by changes in the colloidal particle structure caused by solute-solvent coordination, I - The two-step method for preparing perovskite is caused by the oxidation of organic amine cations, the deprotonation of organic amine cations, and the subsequent reaction between organic amines and organic amine cations. Because PbI2 deposition is controllable, versatile, and flexible, it is easy to obtain a uniform and fully covered PbI2 layer. This step is crucial to improving the quality of perovskite films and further reduces the phenomenon of ion oxidation and protonation in the mixed solution.
[0003] In 1998, Liang et al. obtained MAPbI3 by embedding MAI solution into pre-deposited lead iodide film; in 2013, Burschka et al. applied this method to prepare perovskite photoelectric conversion devices on TiO2 mesoporous layer, and the conversion efficiency reached 15%. Due to its easy operation and high conversion efficiency device reproducibility, it has successfully attracted great attention. Compared with the one-step method, the device reproducibility of the two-step method is higher, but the two-step method is more likely to introduce non-radiative recombination when cation spin coating is applied to perovskite. The morphology of lead iodide directly affects the film quality of perovskite. Insufficient reaction between organic ammonium salt and PbI2 will cause residual PbI2 to cause low crystallinity of perovskite film, and the fragile Pb-I bond is easy to cause iodine loss, reducing the stability of PbI6 skeleton. Huang et al. used 4-fluorobenzylamine (FBA) with C=O and -NH2 in PbI2 precursor solution to regulate the secondary growth process of PbI2 film. The porous PbI2 film has low Gibbs free energy and high crystallinity, which promotes the full reaction between organic ammonium salt and PbI2, thus forming a large-grained, low-defect perovskite film. At the same time, through hydrogen bonding and π-π stacking interactions, the stability of the PbI6 skeleton can be effectively improved, the non-radiative recombination inside the perovskite can be significantly suppressed, and the defect state density can be reduced. Finally, this strategy improves the conversion efficiency of the device from 22.06% to 23.62%, and the modified device still maintains 96% of its initial PCE after being placed in a nitrogen atmosphere for 1300 hours. Liu et al. introduced polyfluoroorganic diammonium octafluoro-([1,1′-biphenyl]-4,4′-diyl)-dimethylmethylammonium (OFPP) iodide, which does not form low-dimensional perovskites, to achieve a discontinuous lead iodide layer, which can better convert lead iodide into perovskite, thereby using OFPP to modulate the crystallinity of the perovskite film and increase the grain size. The modified film enhanced charge mobility and suppressed charge recombination. Finally, the OFPP-based perovskite solar cell achieved a conversion efficiency of 24.76% and better device stability. 2 The large-area perovskite module achieved an excellent conversion efficiency of 21.04%. Summary of the invention
[0004] Purpose of the invention: The first purpose of the present invention is to provide a method for preparing efficient and stable perovskite solar cells based on modified lead iodide, and the technical scheme adopted is as follows:
[0005] A highly efficient and stable perovskite solar cell prepared based on modified lead iodide, characterized in that a TiO2 electron transport layer, a perovskite light absorption layer, a PEAI modification layer, a Spiro-OMeTAD hole transport layer and an Ag electrode layer are sequentially arranged on the front side of a substrate, and the back side of the substrate is a light-transmitting side. The front side of the substrate is the side facing away from the sun when in use, and the back side is a glass light-transmitting side. The material of the substrate is FTO conductive glass, and the length, width and thickness of the substrate are 2 cm, 2 cm and 3 mm respectively.
[0006] Preferably: the thickness of the TiO2 electron transport layer is 200-300nm; the thickness of the perovskite layer is 500-600nm; the thickness of the PEAI modified layer is 200-300nm; the thickness of the Spiro-OMeTAD hole transport layer is 200-300nm; and the thickness of the Al electrode layer is 120nm.
[0007] A method for preparing an efficient and stable perovskite solar cell based on modified lead iodide, characterized in that it comprises the following steps:
[0008] Step a: The substrate is cleaned in an ultrasonic cleaner using detergent, ultrapure water, acetone, and isopropyl alcohol in sequence for 15 minutes, until the added solution covers the substrate;
[0009] Step b: Prepare a TiO2 electron transport layer on the conductive surface of the substrate using a water bath method. Add 45 mg of tartaric acid to 150 mL of ultrapure water, add 3 mL of TiCl4 solution while stirring, then stir for 5-8 minutes, put the prepared TiO2 solution into the beaker to cover the substrate, and finally put the beaker into a 70°C water bath for deposition for 40 minutes;
[0010] Step c: preparing a lead iodide film by spin coating, thermally annealing at 70° C. for 1.5 min, and then dynamically spin coating cations to form a perovskite film, wherein the lead iodide film is a modified lead iodide film, and the preparation method of the modified lead iodide film is as follows:
[0011] Step 1: Prepare 691.5 mg / ml lead iodide solution in a nitrogen glove box, stir until dissolved, add 30 ul of PenAAc, and continue stirring for 3-5 hours;
[0012] Step 2: Spin-coat 50ul of the lead iodide solution prepared in step 1 onto the TiO2 electron transport layer (2) after UV-ozone treatment for 15 minutes at a speed of 3000rpm / min for 30 seconds. The two will react rapidly to form perovskite, and finally anneal on a hot plate at 150°C for 15 minutes.
[0013] Step 3: After the spin coating process is completed, thermal annealing is performed at 70°C for 1.5 minutes to form a modified lead iodide film.
[0014] Step d: Spin-coat a PEAI modification layer on the perovskite film by spin coating: 4 mg of PEAI was dissolved in 1 mL of isopropanol and spin-coated on the perovskite at a speed of 4000 rpm / min for 30 seconds, and then annealed on a hot plate at 60 °C for 5 minutes;
[0015] Step e: Spin-coat a layer of Spiro-OMeTAD hole transport layer on the PEAI modified layer by spin coating, and spin-coat the Spiro-OMeTAD hole transport layer on the PEAI by spin coating at a speed of 4000 rpm / min for 30 seconds. The prepared Spiro-OMeTAD hole transport layer should be oxidized in dry air for 8-10 hours;
[0016] Step f: A 120 nm thick Ag electrode is deposited on the Spiro-OMeTAD hole transport layer by thermal vacuum evaporation. The temperature of the thermal vacuum evaporation coating in step f is 1180-2470°C and the vacuum degree is 9x10 -4 Pa below, the speed of evaporation is The speed of evaporating Ag electrode is The evaporation speed is an important factor affecting the quality of the film. Too fast an evaporation speed may cause uneven film or defects, while too slow an evaporation speed may prolong the production time. Therefore, in practical applications, the evaporation speed needs to be adjusted according to the specific equipment and technical requirements to obtain the best evaporation effect.
[0017] The invention discloses an application of preparing efficient and stable perovskite solar cells based on modified lead iodide.
[0018] Beneficial effects: Compared with the prior art, the present invention has the following significant advantages:
[0019] 1. The present invention prepares high-quality perovskite thin films by directly adding modifying materials into lead iodide, which not only reduces the non-radiative recombination of the entire device, accelerates the transmission of carriers, but also improves various performance parameters of the device, ultimately achieving a photoelectric conversion efficiency of 24.64% for the device.
[0020] 2. The method of the present invention is simple to prepare, has low preparation cost and low time cost.
[0021] 3. The present invention uses amylamine acetic acid to modify lead iodide to form a lead iodide film with high crystallinity and low roughness. The higher crystallinity of PbI2 can further react with cations better, and the lower roughness will prompt the organic salt to react quickly with the surface of PbI2 to form a dense perovskite layer, preventing the formation of formamidinium ions (FA +) Further diffuses into PbI2 and inserts into [PbI6] 4-The modified lead iodide can form a low-defect, high-crystallization perovskite film with cations, further improving the carrier lifetime and accelerating the carrier transport, and finally realizing a perovskite device with high conversion efficiency. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] Figure 1 A schematic diagram of the structure of the perovskite solar cell provided by the present invention;
[0023] Figure 2 Flow chart for preparing perovskite thin films;
[0024] Figure 3 XRD patterns of the lead iodide films prepared in Example 1 and Comparative Example 1;
[0025] Figure 4 AFM images of the lead iodide thin films prepared in Example 1 and Comparative Example 1;
[0026] Figure 5 XRD patterns of the perovskite films prepared in Example 1 and Comparative Example 1;
[0027] Figure 6 The SEM images of the surfaces of the perovskite films prepared in Example 1 and Comparative Example 1;
[0028] Figure 7 AFM images of the surfaces of the perovskite films prepared in Example 1 and Comparative Example 1;
[0029] Figure 8 Voltage diagrams of the perovskite film surfaces prepared in Example 1 and Comparative Example 1;
[0030] Fig. 9 Current diagrams of the surfaces of the perovskite films prepared in Example 1 and Comparative Example 1;
[0031] Fig.10 The dark current images of the perovskite film surfaces prepared in Example 1 and Comparative Example 1;
[0032] Fig.11 JV curves of the perovskite devices prepared in Example 1 and Comparative Example 1; DETAILED DESCRIPTION
[0033] The technical solution of the present invention is further described below in conjunction with the accompanying drawings.
[0034] Example 1
[0035] Preparation of perovskite precursor solution:
[0036] The PbI2 solution was prepared by dissolving 691.5 mg of PbI2 in 1 mL of DMF and DMSO (9:1, v:v), stirring for 4 h to dissolve, and then adding 30 uL of PenAAc, and stirring was continued for another 4 h. The cationic salt precursor solution was prepared by dissolving 12.8 mg of MAI, 18 mg of MACl, and 180 mg of FAI in 2 mL of isopropanol.
[0037] Preparation of perovskite devices:
[0038] 1. Preparation of FTO conductive glass: Clean the FTO conductive glass with detergent, ultrapure water, acetone, and isopropanol for 15 minutes each, then blow dry with a nitrogen gun and put it in a quartz boat for later use. Use a UV ozone machine to clean it for 15 minutes before depositing the electron transport layer.
[0039] 2. Preparation of electron transport layer: Prepare TiO2 electron transport layer on the conductive surface of FTO by water bath method. Add 45 mg of tartaric acid into 150 mL of ultrapure water, add 3 mL of TiCl4 solution while stirring, then stir for 6 minutes, put the prepared TiO2 solution into the base of the beaker to cover it, and finally put the beaker into a 70°C water bath for deposition for 40 minutes.
[0040] 3. Preparation of perovskite film: First, take 50uL of modified lead iodide solution and drop it onto the TiO2 electron transport layer, rotate it at 3000rpm / min for 30s, then anneal it on a hot plate at 70℃ for 1.5min, then dynamically spin-coat the cationic solution on the modified lead iodide at 4000rpm / min for 40s. The two will react rapidly to form perovskite, and finally anneal it on a hot plate at 150℃ for 15min.
[0041] 4. Preparation of PEAI modified layer: 4 mg of PEAI was dissolved in 1 mL of isopropanol and spin-coated on the perovskite at a speed of 4000 rpm / min for 30 s, and then annealed on a hot stage at 60 °C for 5 min.
[0042] 5. Preparation of hole transport layer: 72.3 mg of Spiro-OMeTAD was dissolved in 1 mL of chlorobenzene and stirred until dissolved. 130 mg of LiTFSI was dissolved in 250 mL of acetonitrile and stirred until dissolved. 17.5 uL of LiTFSI solution and 28.8 uL of TBP solution were added to the Spiro-OMeTAD solution and stirred for 4 h. 38.8 uL of doped Spiro-OMeTAD solution was added dropwise to PEAI and rotated at 4500 rpm / min for 30 s.
[0043] 6. Preparation of silver electrode: A 120 nm thick Ag electrode was deposited on the Spiro hole transport layer using vacuum evaporation.
[0044] Example 2
[0045] The difference between the implementation process and Example 1 is that the amount of PenAAc added to the lead iodide is different.
[0046] The PbI2 solution was prepared by dissolving 691.5 mg of PbI2 in 1 mL of DMF and DMSO (9:1, v:v), stirring for 4 h to dissolve, and then adding 20 uL of PenAAc, and stirring was continued for another 4 h. The cationic salt precursor solution was prepared by dissolving 12.8 mg of MAI, 18 mg of MACl, and 180 mg of FAI in 2 mL of isopropanol.
[0047] The perovskite solar cell prepared in this embodiment has a photoelectric conversion efficiency of 24.17%, wherein the short-circuit current is 26.25 mA / cm2, the open-circuit voltage is 1.16 eV, and the fill factor is 79.54%.
[0048] Example 3
[0049] The difference between the implementation process and Example 1 is that the amount of PenAAc added to the lead iodide is different.
[0050] The PbI2 solution was prepared by dissolving 691.5 mg PbI2 in 1 mL DMF and DMSO (9:1, v:v), stirring for 4 h to dissolve, and then adding 25 uL of PenAAc, and stirring was continued for another 4 h. The cationic salt precursor solution was prepared by dissolving 12.8 mg MAI, 18 mg MACl, and 180 mg FAI in 2 mL isopropanol.
[0051] The perovskite solar cell prepared in this embodiment has a photoelectric conversion efficiency of 24.37%, wherein the short-circuit current is 26.80 mA / cm2, the open-circuit voltage is 1.14 eV, and the fill factor is 79.47%.
[0052] Example 4
[0053] The difference between the implementation process and Example 1 is that the amount of PenAAc added to the lead iodide is different.
[0054] The PbI2 solution was prepared by dissolving 691.5 mg PbI2 in 1 mL DMF and DMSO (9:1, v:v), stirring for 4 h to dissolve, then adding 35 uL of PenAAc, and continuing stirring for another 4 h. The cationic salt precursor solution was prepared by dissolving 12.8 mg MAI, 18 mg MACl, and 180 mg FAI in 2 mL isopropanol.
[0055] The perovskite solar cell prepared in this embodiment has a photoelectric conversion efficiency of 24.25%, wherein the short-circuit current is 26.81 mA / cm2, the open-circuit voltage is 1.15 eV, and the fill factor is 78.60%.
[0056] Example 5
[0057] The difference between the implementation process and Example 1 is that the amount of PenAAc added to the lead iodide is different.
[0058] The PbI2 solution was prepared by dissolving 691.5 mg PbI2 in 1 mL DMF and DMSO (9:1, v:v), stirring for 4 h to dissolve, then adding 40 uL of PenAAc, and continuing stirring for another 4 h. The cationic salt precursor solution was prepared by dissolving 12.8 mg MAI, 18 mg MACl, and 180 mg FAI in 2 mL isopropanol.
[0059] The perovskite solar cell prepared in this embodiment has a photoelectric conversion efficiency of 23.89%, wherein the short-circuit current is 26.27 mA / cm2, the open-circuit voltage is 1.15 eV, and the fill factor is 79.21%.
[0060] Comparative Example 1
[0061] Same as Example 1, except that:
[0062] When the perovskite precursor solution was prepared, PenAAc was not added to the lead iodide solution.
[0063] Effect Example 1 Effect of the introduction of PenAAc on the crystallinity of lead iodide
[0064] XRD characterization: XRD is used to observe the crystallization of lead iodide.
[0065] from Figure 3 It can be seen that after PenAAc modification, the peak intensity of the lead iodide peak near 15° increased significantly, indicating that the crystallinity of lead iodide was improved.
[0066] AFM characterization: Atomic force microscopy can be used to obtain high-resolution images of surface morphology, including surface undulations, grooves, particle size and other features. Surface roughness can also be measured through the amplitude and frequency of tiny undulations and ripples.
[0067] from Figure 4 It can be seen that after PenAAc modification, the surface roughness of PbI2 is reduced from 7.71nm to 6.57nm. The lower roughness will prompt the organic salt to react quickly on the surface of PbI2 to form a dense perovskite layer, preventing the formation of formamidinium ions (FA + ) further diffuses into PbI2 and inserts into [PbI6] 4-skeleton, which eventually leads to the decrease of crystallinity of perovskite film.
[0068] XRD characterization: XRD is used to observe the crystallization of each crystal face of perovskite.
[0069] from Figure 5 It can be seen that after PenAAc modification, the crystallinity of the (100) and (200) planes of the perovskite is greatly enhanced, indicating that the crystallization quality of the perovskite film is improved, and there is almost no lead iodide residue in the modified film. Figure 6 The SEM image can also better confirm this point. Compared with comparative example 1, the perovskite film of Example 1 has a larger crystal size and a more uniform grain distribution. The residual lead iodide can also be clearly seen in comparative example 1. Excessive residual lead iodide in the perovskite film will induce further decomposition of the perovskite. Figure 7 From the two-dimensional roughness map of the perovskite, it can be clearly seen that the surface roughness of the perovskite formed by the modified lead iodide is reduced from 34.8nm to 26nm, and the surface is smoother than that of comparative example 1, and there is not much residue on the surface.
[0070] KPFM: Measure the surface potential distribution of the sample, the results are as follows Figure 8 shown.
[0071] CAFM: measures the current distribution on the sample surface, such as Fig. 9 shown.
[0072] from Figure 8 It can be seen that the surface potential of Example 1 is relatively low, and the distribution is more uniform than that of Comparative Example 1. The lower and more uniform potential distribution on the perovskite surface is more conducive to the transmission of carriers, and will eventually increase the current on the perovskite surface. Fig. 9 As shown, the surface current of Example 1 increases, indicating that the non-radiative recombination inside the perovskite decreases.
[0073] Dark current: The smaller the leakage current, the fewer defects in the device. The test results are as follows: Fig.10 shown.
[0074] Fig.10 This is a dark current comparison diagram of Example 1 and Comparative Example 1. It can be seen that the leakage current of Example 1 is much smaller than that of Comparative Example 1. It can be seen that the modified lead iodide promotes the further formation of a perovskite film with low defect density, further reducing the non-radiative recombination inside the device.
[0075] Perovskite battery performance test
[0076] Test conditions: The perovskite cells prepared in the examples and comparative examples were tested at AM1.5G, 100mW / cm 2The current density-voltage (JV) performance curve of the battery tested under light, such as Fig.11 , the test data are shown in Table 1.
[0077] Table 1
[0078] Test subjects <![CDATA[Short-circuit current density (mA / cm 2 )]]> Open circuit voltage(V) Fill Factor Photoelectric conversion efficiency Example 1 26.59 1.14 81.51% 24.64% Example 2 26.25 1.16 76.97% 24.17% Example 3 26.80 1.14 79.47% 24.37% Example 4 26.81 1.15 78.60% 24.25% Example 5 26.27 1.15 79.21% 23.89% Comparative Example 1 26.09 1.13 76.97% 22.59%
[0079] Fig.11 JV curves of the perovskite cells prepared in Example 1 and Comparative Example 1.
[0080] from Fig.11 As can be seen from the data in Table 1, the introduction of PenAAc can improve the photoelectric performance of perovskite solar cell devices, mainly because the cations and lead iodide fully react to form a perovskite film with high crystallinity and low defect density, thereby accelerating the internal carrier transport of the perovskite and reducing the internal non-radiative recombination, thereby reducing unnecessary energy loss.
Claims
1. A method for preparing an efficient and stable perovskite solar cell based on modified lead iodide, characterized in that: The front side of the substrate (1) is provided with a TiO2 electron transport layer (2), a perovskite light absorption layer (3), a PEAI modification layer (4), a Spiro-OMeTAD hole transport layer (5) and an Ag electrode (6) in sequence, and the back side of the substrate (1) is a light-transmitting side. The front side of the substrate (1) is the side facing away from the sun when in use, and the back side is a glass light-transmitting side. The material of the substrate (1) is FTO conductive glass.
2. The method for preparing an efficient and stable perovskite solar cell based on modified lead iodide according to claim 1, characterized in that: The substrate (1) has a length of 2 cm, a width of 2 cm and a thickness of 3 mm.
3. The method for preparing an efficient and stable perovskite solar cell based on modified lead iodide according to claim 1, characterized in that: The thickness of the TiO2 electron transport layer (2) is 200-300 nm; The thickness of the perovskite layer (3) is 500-600 nm; The thickness of the PEAI modified layer (4) is 200-300 nm; The thickness of the Spiro-OMeTAD hole transport layer (5) is 200-300 nm; The thickness of the Ag electrode (6) is 120 nm.
4. The method for preparing an efficient and stable perovskite solar cell based on modified lead iodide according to any one of claims 1 to 3, characterized in that: The following steps are involved: Step a: The substrate (1) is cleaned in an ultrasonic cleaning machine using detergent, ultrapure water, acetone, and isopropanol in sequence for 15 minutes; Step b: preparing a TiO2 electron transport layer (2) on the conductive surface of the substrate (1) by a water bath method; Step c: preparing a lead iodide film by spin coating, thermally annealing at 70° C. for 1.5 min, and then dynamically spin coating cations to form a perovskite film (3); Step d: Spin coating a PEAI modified layer (4) on the perovskite film (3) by spin coating; Step e: Spin coating a layer of Spiro-OMeTAD hole transport layer (5) on the PEAI modified layer (4) by spin coating; Step f: Using a thermal vacuum evaporation coating method, a 120 nm thick Ag electrode (6) is deposited on the Spiro-OMeTAD hole transport layer.
5. The method for preparing an efficient and stable perovskite solar cell based on modified lead iodide according to claim 4, characterized in that: The lead iodide film in step c is a modified lead iodide film.
6. The method for preparing an efficient and stable perovskite solar cell based on modified lead iodide according to claim 5, characterized in that: The lead iodide film modification method comprises the following steps: Step 1: Prepare the lead iodide solution in a nitrogen glove box, stir until dissolved, then add PenAAc and continue stirring for 3-5h; Step 2: Spin-coat the lead iodide solution prepared in step 1 onto the TiO2 electron transport layer (2) after UV-ozone treatment for 15 minutes at a rotation speed of 3000 rpm / min for 30 seconds; Step 3: After the spin coating process is completed, thermal annealing is performed at 70°C for 1.5 minutes to form a modified lead iodide film.
7. The method for preparing an efficient and stable perovskite solar cell based on modified lead iodide according to claim 5, characterized in that: Step f: The temperature of the thermal vacuum evaporation coating is 1180-2470°C and the vacuum degree is 9x10 -4 Pa below, the speed of evaporation is The speed of evaporating Ag electrode is
Citation Information
Cited By
Direct X-ray detector based on one-dimensional bismuth-based perovskite material and preparation method
CN119997784A